Determination Some biological characteristics of Chondrostoma regium (Heckel, 1843) in Tishreen Lake (Euphrates River) (Latakia University Journal -Biological Sciences Series, 2020)
This study was conducted to determine the sexual and age compositions, the relationship of  length and weight  with age, weight- - length relationship and the condition factor according to age  groups of 309 Chondrostoma regium (Heckel, 1843) individuals collected  from Tishreen  Lake  between  April 2010 to May 2012. Individuals ranged between (I-VI) age group, were females that constituted 50.80% while males were 41.74%. The first and second age groups were dominated  all  samples with a rate of 68.93% . The length ranged between 9.70-28.34 cm and the majority were between 11-17 cm  while the weight was distributed between 17.47-234.92 g and the majority was between 25-95 g.Length and weight relationships the age were estimated and the equations were: ،  The relationship of weight to length was: ،The condition factor had the highest value (1.35) at the age group IV 1.35 while the lowest value(0.78) was at the age group I.